2021
DOI: 10.1186/s13052-021-01079-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pediatric integrative manual therapy in positional plagiocephaly: a randomized controlled trial

Abstract: Background Positional plagiocephaly frequently affects healthy babies. It is hypothesized that manual therapy tailored to pediatrics is more effective in improving plagiocephalic cranial asymmetry than just repositioning and sensory and motor stimulation. Methods Thirty-four neurologically healthy subjects aged less than 28 weeks old with a difference of at least 5 mm between cranial diagonal diameters were randomly distributed into 2 groups. For 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
1
9
0
2
Order By: Relevance
“…This is different from research comparing other interventions to usual care, where other interventions showed greater bene ts 62 , for example, manual therapy and repositioning therapy when compared with usual care 3,39 . These ndings con ict with the conclusions from two recent RCTs 75,76 which reported a signi cant reduction in CVAI and increase in CROM in infants diagnosed with moderate to severe HSA. These were infants who received manual therapy in addition to HCP delivered guidance compared with those who received the HCP guidance alone.…”
Section: Limitationssupporting
confidence: 59%
“…This is different from research comparing other interventions to usual care, where other interventions showed greater bene ts 62 , for example, manual therapy and repositioning therapy when compared with usual care 3,39 . These ndings con ict with the conclusions from two recent RCTs 75,76 which reported a signi cant reduction in CVAI and increase in CROM in infants diagnosed with moderate to severe HSA. These were infants who received manual therapy in addition to HCP delivered guidance compared with those who received the HCP guidance alone.…”
Section: Limitationssupporting
confidence: 59%
“…We focused on CA in this study; nevertheless, the severity is defined using CVAI in other previous studies [3,15,19,20] (e.g., mild, 5-6%; moderate, 7-9%; severe, 10-13%; and very severe, >14%) [3,15]. The median CVAI exceeded 10% in both the natural-course and CHT groups in this study 2, indicating a severe plagiocephaly.…”
Section: Discussionmentioning
confidence: 90%
“…El tratamiento de la plagiocefalia va dirigido a favorecer el apoyo de la cabeza en el lado no afectado. El manejo a través de posicionamiento cefálico, estimulación del desarrollo motor y kinesiología, tienen una fuerte evidencia 21,[48][49][50][51] . Sólo algunos casos muy seleccionados podrían beneficiarse del uso de casco modelador, como se describirá más adelante.…”
Section: Tratamientounclassified
“…Otro método utilizado es la manipulación osteopática que pretende movilizar todas las estructuras comprometidas (ej. fascia y músculos cervicales) con movimientos suaves para restablecer el balance normal del cuerpo 48,50 .…”
Section: Tratamientounclassified